KEHIDUPAN SOSIAL EKONOMI MASYARAKAT PENAMBANG EMAS DI NAGARI LUBUK GADANG KECAMATAN SANGIR KEBUPATEN SOLOK SELATAN TAHUN 2007-2012 - rianto, Agus; Nurhuda, Ahmad; Aziz, Zulkifli (Pendidikan Sejarah, 2014)
This studyexamines thechanges insocial and economic lifeof gold miners in Nagari Lubuk Sangir Tower District of South Solokof West Sumatra province. Socio-economic changes are directedtothe gold minersin theTower District of Sangir Lubuk Nagari. The purposeof this study is to explain what changes occurin the gold mining community in Nagari Lubuk Tower. Life ofgold miners in Nagari Lubuk Tower, the influence of gold mining on the social and economic life of gold miners in Nagari Lubuk Sangir Tower District of South Solok years 2007-2012. The method used in this research is the study of history , the phase - phase as follows : The first heuristic is collecting data from relevant sources . The second source of criticism .selecting a source in accordance with the needs of research . The third interpretation is the sorting step - out or distinguish the source of history .so that the granules found real information . Fourth historiography which wrote the studys findings into written form in accordance with the rules of scientific historical research .The results showed that work as gold miners have little impact on the socio-economic life of the miners , that rising incomes . In comparison to before the job up as a miner with rising incomes make their lives better .fulfillment of economic needs of miners . mining community can build their homes to be better than the previous , more miners are eager to send their children , they are to a higher level , such as junior high school, to college , and , increase their awareness of the importance of education for them. Conclusion villagers socio-economic changes Lubuk Tower gold miners in 2007 - 2012 experienced a significant change , it can be seen from various aspects , namely in terms of revenue earning gold miners are increasing and their lives change when viewed from the start of their childs education level of TK / RA to the university , from the aspects of life viewed from the residential buildings of the miners who have gold miners machine building them a permanent home and a minimalistÂ